The problem with everything : my journey through the new culture wars - Daum, Meghan, 1970- (Gallery Books, 2019)
"A book blending memoir, reporting, and argument, which drills past the obvious political opinions of our moment in an attempt to make sense of our social and political landscape, particularly with regards to feminism and the various layers of the Trump Resistance movement"--